Performance management: strategies, interventions, drivers - Kandula, Srinivas R.
Of all the human resource management functions, performance management is the most critical function for all organizations intending to enrich the worth of the human capital as well as deliver profits to all stakeholders as a consistent practice. It is adopted by organizations in rewarding good performance, developing employees, and addressing performance concerns. This comprehensive book, written from practitioner's point of view, presents the theory and practices of performance management in a systematic manner. The book is patterned after motivational structure of human resource comprising seven strategies - Reward, Career, Team, Culture, Measurement, Competency and Leadership centric performance management, 14 interventions, and 140 drivers. It discusses in detail important topics such as the 360 degree feedback, the balanced scorecard, six sigma, implementing performance management model/appraisal system, which are essentials of successful performance management.